The euro and international capital markets - Carsten Detken; Philipp Hartmann (Goethe University Frankfurt, Center for Financial Studies (CFS), 2000)
This paper provides a broad empirical examination of the major currencies' roles in international capital markets, with a special emphasis on the first year of the euro. A contribution is made as to how to measure these roles, both for international financing as well as for international investment. The times series collected for these measures allow for the identification of changes in the role of the euro during 1999 compared to the aggregate of euro predecessor currencies, net of intra -euro area assets/liabilities, before stage 3 of EMU. A number of key factors determining the currency distribution of international portfolio investments, such as relative market liquidity and relative risk characteristics of assets, are also examined empirically. It turns out that for almost all important market segments for which data are available, the euro immediately became the second most widely used currency for international financing and investment. For the flow of international bond and note issuance it experienced significant growth in 1999 even slightly overtaking the US dollar in the second half of the year. The euro's international investment role appears more static though, since most of the early external asset supply in euro is actually absorbed by euro area residents.
urn:nbn:de:hebis:30-9731
Keywords: G15; F32; G11; F21; 330; international capital markets; international currencies; euro; dollar; yen; EMU; capital flows; international monetary system; portfolio selec